Esl Learners’ Experiences With Web-Based Concordance In Facilitating Phrasal Verbs Acquisition - Zaini, Khazaila (2021)
This study endeavours to explore the usefulness of web-based concordance in acquiring English phrasal verbs. The whole thesis was primarily conducted in the qualitative method but it involved a quantitative test in the first stage to get the general understanding of students’ phrasal verbs proficiency level which later followed by a qualitative approach using think-aloud protocol and thematic analysis. The study reveals aspects of corpus use by thirty students at a private university in Kuala Lumpur, Malaysia. The students were asked to consult the web-based concordance during the ten weeks of web-based concordance intervention. Firstly, students’ performance differences in phrasal verbs comprehension were examined between their pre-and post-tests. Secondly, students’ problem-solving processes and thinking strategies were explored while analysing data on the web-based concordance. Thirdly, the students’ experiences using web-based concordance on phrasal verbs acquisition and writing were explored. Twelve focal students from three different English levels: upper-intermediate, intermediate and lower-intermediate were selected as focal students. Pre-test and post-test tests show that approximately 92% of students showed an increase in their scores. Overall results indicated that the participants validated the benefits of using web-based concordance. Finally, the study provides pedagogical and future research recommendations for incorporating the use of web-based concordance in acquiring phrasal verbs.